2019
DOI: 10.1111/sjpe.12190
|View full text |Cite
|
Sign up to set email alerts
|

Global Determinants of the Gold Price: A Multivariate Cointegration Analysis

Abstract: The present paper follows publications which have investigated the influence of global liquidity developments on commodity prices and asset price indices. It contributes to the literature by analyzing how global developments in money, output, and inflation can be related to developments in gold prices in a long-run perspective. Applying a multivariate cointegration (CVAR) analysis, this study investigates long-run relationships between these variables. The results suggest a significant influence of excess glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In order to discuss this proposition the following author's inputs were taken into account (see O'Connor et al (2015))s: Jaffe (1989) regressed the return on gold with the changes in CPI for the period between 1971 and 1987, he found a positive relation between the price of gold and movements in the price level although he points out the significance is very small; Naser (2017) takes Bodie (1976) (Bodie's focus was on the minimum variance point along the efficient portfolio frontier concluding that an hedge against inflation is any security that reduces the variance of the real return of a nominal risk-free bond) definition of what type of security can be considered an inflation hedge and uses Fisher's equation (see Fisher (1930)) under a rational expectations' framework for US monthly data from 1986 to 2016, employed into an error correcting model (ECM) developed by Johansen (1988) and Johansen & Juselius (1990) in order to examine the long and short term relationship between gold's returns and inflation as measured by the CPI for all urban consumers. His findings suggest gold is not a short-term hedge against inflation but that it can be so for investors willing to hold gold for longer periods; Murach (2019) used quarterly data for thirteen countries (The EU was taken as a country for monetary purposes) from 1980 to 2013. By applying a multivariate cointegration (CVAR) analysis, he found that there is a positive long-run relationship between global liquidity and the price of gold, where the author defines "global liquidity" as the difference between money in a broader sense and nominal GDP, .…”
Section: Related Literaturementioning
confidence: 99%
“…In order to discuss this proposition the following author's inputs were taken into account (see O'Connor et al (2015))s: Jaffe (1989) regressed the return on gold with the changes in CPI for the period between 1971 and 1987, he found a positive relation between the price of gold and movements in the price level although he points out the significance is very small; Naser (2017) takes Bodie (1976) (Bodie's focus was on the minimum variance point along the efficient portfolio frontier concluding that an hedge against inflation is any security that reduces the variance of the real return of a nominal risk-free bond) definition of what type of security can be considered an inflation hedge and uses Fisher's equation (see Fisher (1930)) under a rational expectations' framework for US monthly data from 1986 to 2016, employed into an error correcting model (ECM) developed by Johansen (1988) and Johansen & Juselius (1990) in order to examine the long and short term relationship between gold's returns and inflation as measured by the CPI for all urban consumers. His findings suggest gold is not a short-term hedge against inflation but that it can be so for investors willing to hold gold for longer periods; Murach (2019) used quarterly data for thirteen countries (The EU was taken as a country for monetary purposes) from 1980 to 2013. By applying a multivariate cointegration (CVAR) analysis, he found that there is a positive long-run relationship between global liquidity and the price of gold, where the author defines "global liquidity" as the difference between money in a broader sense and nominal GDP, .…”
Section: Related Literaturementioning
confidence: 99%
“…Murach () provides a different angle in the gold market by focusing on long‐run determinants. His research extends earlier work which investigated the influence of global liquidity developments on commodity prices and different asset prices.…”
mentioning
confidence: 99%